200 Effects of Bull/Cow Trim and Finely Texture Beef on Cooked Color. (10th April 2018) - Althaber, C A; Apple, J A; Yancey, J W S; Johnson, T; Glascock, T W
Abstract: Variation in internal cooked color of ground beef is of an economic concern for many sectors of the ground beef market. Persistent pink color in hamburger patties, even after reaching an internal temperature of 71°C, can lead consumers to the perception of an undercooked product. Therefore, the objective of this study was to characterize the effects of bull/cow blend proportions, with or without finely textured beef (FTB), on internal cooked color of precooked ground beef patties. Batches of lean (85%) ground beef were manufactured with 0, 33, 67, or 100% bull/cow blend (remainder of the lean was 100, 67, 33, or 0% Select-grade knuckles, respectively) mixed with 2 kg of 50:50 beef trim and 0 or 15% FTB, resulting in 8 replicates of 8 treatment formulations. Each batch was mixed in a commercial mixer-grinder for 5 min before being ground through a 0.95-cm plate, and formed into 150-g patties (40/batch). Fresh color (L*, a*, and b*) was measured before patties were cooked in an impingement oven to internal temperature of 71°C, and submerged in an ice bath before measuring internal cooked color (L*, a*, and b*). The next day, refrigerated cooked patties were reheated to an internal endpoint temperature of 71°C on a char-grill (CHAR) or in either a clam-shell griddle (PAN) or forced-air convection oven (OVEN) before measuring internal reheated color. Data were analyzed as a 4 × 2 factorial design with PROC GLIMMIX of SAS. Fresh patties became darker, less red, and more yellow (linear, P≤0.012) with increasing proportions of bull/cow blend, whereas FTB addition increased (P<0.05) L* values and decreased (P<0.05) a* and b* values of fresh patties. Cooked patties became darker (linear, P<0.001) with increasing bull/cow blend, and addition of FTB reduced (P<0.05) internal cooked redness (a*) and yellowness (b*) of patties. Reheated L* values decreased with increasing bull/cow blend percentages (linear, P<0.001), and inclusion of FTB reduced (P<0.05) a* values in reheated patties. Also, patties reheated in OVEN were lighter (P<0.05) and more red (P<0.05) and yellow (P<0.05) than patties reheated in PAN or on CHAR. There were no (P≥0.153) blend × FTB interactions for fresh, cooked or reheated color of patties. Further research is needed to evaluate more methods of abating pink color in recooked hamburger patties.